2017
DOI: 10.1038/srep40791
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 antagonist FP7 inhibits LPS-induced cytokine production and glycolytic reprogramming in dendritic cells, and protects mice from lethal influenza infection

Abstract: Dysregulated Toll-like receptor (TLR)-4 activation is involved in acute systemic sepsis, chronic inflammatory diseases, such as atherosclerosis and diabetes, and in viral infections, such as influenza infection. Thus, therapeutic control of the TLR4 signalling pathway is of major interest. Here we tested the activity of the small-molecule synthetic TLR4 antagonist, FP7, in vitro on human monocytes and monocyte-derived dendritic cells (DCs) and in vivo during influenza virus infection of mice. Our results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(132 citation statements)
references
References 61 publications
3
128
0
1
Order By: Relevance
“…The mechanism of action is based on direct competition with LPS for interacting with the MD‐2 binding pocket . We recently observed that FP7 targets selectively TLR4 and not TLR2, and that it is able to block the TLR4 signal activated by microbial PAMPs and also by endogenous DAMPs such as HMGB1 protein . The potent and selective TLR4 antagonist activity and its lack of toxicity make FP7 a good lead for therapeutic development against pathologies generated by PAMP–TLR4 and DAMP–TLR4 signaling.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The mechanism of action is based on direct competition with LPS for interacting with the MD‐2 binding pocket . We recently observed that FP7 targets selectively TLR4 and not TLR2, and that it is able to block the TLR4 signal activated by microbial PAMPs and also by endogenous DAMPs such as HMGB1 protein . The potent and selective TLR4 antagonist activity and its lack of toxicity make FP7 a good lead for therapeutic development against pathologies generated by PAMP–TLR4 and DAMP–TLR4 signaling.…”
Section: Resultssupporting
confidence: 73%
“…We recently synthesized FP7 (Figure ), a diphosphorylated glucosamine monosaccharide bearing two myristic (C 14 ) chains linked to the C‐2 and C‐3 positions, which was shown to be active as a TLR4 antagonist in cells and in animal models . Similarly to disaccharide‐based lipid A mimetics that block TLR4, such as eritoran, FP7 binds to MD‐2 by inserting its fatty acid C 14 linear chains into the receptor's binding cavity .…”
Section: Introductionmentioning
confidence: 99%
“…In further support of the role of oxidized phospholipids in mediating TLR4-dependent lethality, mortality can be prevented by inhibiting oxidized phospholipid formation by administering the antioxidant N-acetyl cysteine [64]. Additionally, we reported that mortality can be prevented by inhibiting TLR4 signaling after PR8 infection with the potent synthetic TLR4 antagonist Eritoran [20], an anti-TLR4 Ab [25], and other agents that block TLR4 signaling [26,27]. Thus, we hypothesized that drugs that target host-cell, TLR4-dependent signaling pathways could potentially function as novel anti-influenza therapies.…”
Section: Discussionmentioning
confidence: 67%
“…Blocking TLR4 signaling on d 2 or on d 2 and d 4 after PR8 infection with an anti-TLR4-specific Ab also conferred protection [25]. These and other TLR4 antagonists identified by our group [26,27] indicate that TLR4 antagonists may represent a novel class of drugs for use in treating patients with influenza.…”
Section: Introductionmentioning
confidence: 74%
“…Moreover, a significant degree of survival was observed even when eritoran was administered to PR8-infected mice starting as late as day 6 post-infection. Protection against influenza infection was confirmed using other TLR4 antagonists including an anti-TLR4-specific antibody, TLR4 cell-permeable decoy peptides, a structural analog antagonist (FP7), and the small molecule TLR4 antagonist, TAK242 (Perrin-Cocon et al, 2017;Piao et al, 2015). Eritoran was also protective in cotton rats (Sigmodon hispidus) infected with non-adapted human influenza A and B strains.…”
Section: Preclinical Topicsmentioning
confidence: 94%